Biosorption of Indigo Carmine onto Duck Egg White-Modified Longan Peel Biosorbent: Effect of Particle Size and Contact Time - Waarsyat, Fadli; Kurniawati, Desy; Etika, Sri Benti; Sari, Trisna Kumala; Husein, Saddam; Jeningsih; Septian Budiman (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
The increasing demand in the textile industry ideally requires effective wastewater treatment systems to prevent environmental pollution. These pollutants are resistant to degradation and pose serious risks to aquatic ecosystems and human health. To address this issue, sustainable and low-cost treatment methods are urgently needed. Biosorption using agricultural waste has emerged as a promising alternative; however its performance is often limited by insufficient active binding sites. Therefore, surface modification using natural protein sources is proposed to enhance adsorption capacity and efficiency. This study aims to develop and evaluate longan peel modified with duck egg white (LP-DEW) as an eco-friendly biosorbent for indigo carmine removal. The effects of particle size and contact time were investigated, and adsorption kinetics were analyzed using pseudo-first-order, pseudo-second-order, and intraparticle diffusion models. The results showed that LP-DEW exhibited a maximum adsorption capacity of 128.27 mg g-1 at an optimal particle size of 63 μm and equilibrium time of 90 min. The adsorption process followed the pseudo-second-order model, indicating chemisorption as the dominant mechanism. In conclusion, LP-DEW demonstrates high adsorption efficiency and favorable kinetics, highlighting its potential as a sustainable biosorbent for dye-contaminated wastewater treatment.